2005
DOI: 10.1177/0883911505051855
|View full text |Cite
|
Sign up to set email alerts
|

Gel Beads Composed of Chitosan and Polyacids and Their Blood Compatibility

Abstract: Chitosan gel beads were prepared as a model for new chitosan materials and their blood compatibility was evaluated in vitro in human pool plasma and in human whole blood. The one-stage method for the preparation of monolithic beads consisted of performing a template polymerization of 2-acryloylamido-2-methylpropanesulfonic acid (AMPS) or copolymerization of AMPS and acrylic acid. Monolithic beads of semi-interpenetrating networks chitosan/copolymer were prepared in the presence of a cross-linking agent. The eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Often, the behavior of polymer materials on contact with blood is evaluated by SEM study of blood cell adhesion after in vitro contact of the material with blood 6, 28, 29. In the present study, the effect of chitosan coating and the presence of PEG in the fibers on the behavior of PLLA and PLLA/PEG mats on contact with blood were estimated.…”
Section: Resultsmentioning
confidence: 95%
“…Often, the behavior of polymer materials on contact with blood is evaluated by SEM study of blood cell adhesion after in vitro contact of the material with blood 6, 28, 29. In the present study, the effect of chitosan coating and the presence of PEG in the fibers on the behavior of PLLA and PLLA/PEG mats on contact with blood were estimated.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, some of us have shown that PAMPSNa possesses anticoagulant activity comparable to that of the natural anticoagulant heparin14 and its complex formation with haemostatic polymers leads to polymer materials with improved blood compatibility 11. We have studied the complex formation between (quaternized) PDMAEMA and PAMPSNa 22.…”
Section: Resultsmentioning
confidence: 99%
“…The time for clot formation was determined after mixing the plasma with the corresponding reagent (STA Neoplastin® Plus, STA Thrombin, STA APTT Kaolin, STA Fibrinogen, or STA Antithrombin III). The data obtained from the clottability assay was processed using the following equations in accordance with already reported studies:11, 23 where PT c , TT c , APTT c , Fibrinogen c , and ATIII c are the values of the haemostatic parameters in the presence of CECh or (quaternized) PDMAEMA and PT 0 , TT 0 , APTT 0 , Fibrinogen 0 , and ATIII 0 are those of the controls in the absence of polymers. The concentration of the polymers was in the range of 8–16 mg · mL −1 in the total volume.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be biocompatible and has been used successfully in a range of applications from drug delivery [13,15] to cell implantation in vivo [16,17]. Carboxymethyl cellulose (CMC) is also a derivative of cellulose, which is often used as thickener and additive in the food and chemical industries.…”
Section: Introductionmentioning
confidence: 99%